Components in Lesson Planning for Secondary School Teachers in Tanzania: Implications for Supervision and Teachers’ Training - Omollo, Abich; Matete, Rose; Loisulie, Paul (Educational Challenges, 2024)
Purpose. The purpose of the study was to identify specific components of a lesson plan that teachers struggle to design. Methodology. The study used a qualitative research approach and an exploratory case study design. The criterion-purposeful sampling technique was employed to select eighteen (18) participants from six public secondary schools in the Kilimanjaro region of Tanzania. The study participants comprised six heads of secondary schools, six internal school quality assurance officers, and six teachers. Through semi-structured interviews and document reviews, data on specific components of the lesson plan that teachers find challenging to design was collected. The reviewed documents included school performance evaluation reports (SPERs) and lesson plans. The researchers employed thematic analysis methods. The study also followed all necessary principles of research ethics, including obtaining participants’ consent and employing pseudonyms. Results. The study found that teachers were struggling in formulating a coherent statement of specific lesson objectives, teaching and learning materials, and teaching and learning activities. The study also demonstrated that teachers faced difficulties in selecting effective teaching and learning approach, establishing assessment criteria, and conducting proper lesson evaluation. Conclusion. We conclude that inadequate design of one component of the lesson plan negatively affects the overall quality of the lesson plan, the delivery of lessons in the classroom, and the quality of education. Therefore, instructional supervisors and teacher trainers must take immediate action to assist teachers in developing lesson planning skills. This endeavour will not only result in improved lesson planning and delivery by teachers, but it will also contribute to an overall improvement in student learning and educational quality.